The Role of Lifestyle and Dietary Factors in the Development of Premature Ovarian Insufficiency - Shelling AN; Ahmed Nasef N (MDPI (Basel, Switzerland), 2023)
Premature ovarian insufficiency (POI) is a condition that arises from dysfunction or early depletion of the ovarian follicle pool accompanied by an earlier-than-normal loss of fertility in young women. Oxidative stress has been suggested as an important factor in the decline of fertility in women and POI. In this review, we discuss the mechanisms of oxidative stress implicated in ovarian ageing and dysfunction in relation to POI, in particular mitochondrial dysfunction, apoptosis and inflammation. Genetic defects, autoimmunity and chemotherapy, are some of the reviewed hallmarks of POI that can lead to increased oxidative stress. Additionally, we highlight lifestyle factors, including diet, low energy availability and BMI, that can increase the risk of POI. The final section of this review discusses dietary factors associated with POI, including consumption of oily fish, mitochondria nutrient therapy, melatonin, dairy and vitamins that can be targeted as potential interventions, especially for at-risk women and in combination with personalised nutrition. Understanding the impact of lifestyle and its implications for POI and oxidative stress holds great promise in reducing the burden of this condition.
Keywords: diet; early menopause; infertility; lifestyle; ovarian ageing; oxidative stress; premature ovarian insufficiency